Sample collection for human genetics - Dean, Michael (Henry Stewart Talks, 2007)
DNA collection and isolation, Approaches to human genetics, Complex diseases, Example of a Mendelian disease gene that led to a complex disease gene, ABCA4: Stargardt Disease and age-related macular degeneration, Degeneration example of complement genes and retinal degeneration, Infectious disease and host response genes, CCR5 and HIV-1 resistance and AIDS progression: common variants, rare variants or both?
Archived at 2018/10/28